Multispecies Evaluation of a Long-Acting Tenofovir Alafenamide Subdermal Implant for HIV Prophylaxis - Gunawardana, Manjula; Remedios-Chan, Mariana; Sanchez, Debbie; Webster, Simon; Galvan, Patricia; Fanter, Rob; Castonguay, Amalia E.; Webster, Paul; Moss, John A.; Kuo, Joseph; Gallay, Philippe A.; Vincent, Kathleen L.; et al. (Frontiers in Pharmacology, 2020)
New HIV-1 infection rates far outpace the targets set by global health organizations, despite important progress in curbing the progression of the epidemic. Long-acting (LA) formulations delivering antiretroviral (ARV) agents for HIV-1 pre-exposure prophylaxis (PrEP) hold significant promise, potentially facilitating adherence due to reduced dosing frequency compared to oral regimens. We have developed a subdermal implant delivering the potent ARV drug tenofovir alafenamide that could provide protection from HIV-1 infection for six months, or longer. Implants from the same lot were investigated in mice and sheep for local safety and pharmacokinetics (PKs). Our is the first report using these animal models to evaluate subdermal implants for HIV-1 PrEP. The devices appeared safe, and the plasma PKs as well as the drug and metabolite concentrations in dermal tissue adjacent to the implants were studied and contrasted in two models spanning the extremes of the body weight spectrum. Drug and drug metabolite concentrations in dermal tissue are key in assessing local exposure and any toxicity related to the active agent. Based on our analysis, both animal models were shown to hold significant promise in LA product development.